Harmonizing Identities: Language's Role in Shaping 'The Sounds of Islamic Identity' - Salawat Dulang Alam and Qodratullah (Harmonisasi Identitas: Peran Bahasa dalam Membentuk 'Suara Identitas Islam' - Salawat Dulang Alam dan Qodratullah) - Firdaus Firdaus; Riswani Riswani; Syafniati Syafniati; Firman Firman; Jufri Jufri (Jurnal Gramatika, 2023)
This article explores the transformation of the text Salawat Dulang Alam and Qodratullah music into a new artwork form that embodies the narrative form of Islamic identity in West Sumatra. The research involved a collaborative work of transformation by practitioners of Salawat Dulang. The Festival Musica Sacral committee commissioned the creation of this musical artwork, and the artists created new performances with new texts following the theme requested by the committee. The production was done by adopting contemporary songs and inserting theatrical elements that collaborated with traditional Salawat Dulang song texts, highlighting the role of language as identity. The research resulted in a new form of Salawat Dulang music that is more communicative and touches the heartstrings. Incorporating contemporary text songs and theatrical elements created a fresh perspective on Salawat Dulang music, embodying Islamic identity's narrative form in West Sumatra. The study suggests that transforming traditional art forms into contemporary ones can create a new way of looking at the art form, leading to increased communication and emotional connection with the audience. It is also suggested that further research should be carried out to explore the possibilities of transforming other traditional art forms similarly, recognizing the role of language as a vital component of identity.